Formulation and Evaluation of Antioxidant Activity of Instant Granules from 70% Ethanol Extract of Single Black Garlic (Allium sativum L.) - Setiawan, Abdul Aziz; Yuniarto, Ari; Taptajani, Emir Rizky (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Free radicals contribute to various diseases by inducing oxidative stress. Single black garlic (Allium sativum L.) is recognized for its phenolic compounds, which possess radical-scavenging properties. This study aimed to develop and evaluate instant granules containing black A. sativum extract for their antioxidant activity and physicochemical characteristics. An instant granule formulation was developed using a 70% ethanol extract of a single black A. sativum, with three distinct formulas containing 5%, 7.5%, and 10% extract (Formulas 1, 2, and 3, respectively). The granules were subjected to comprehensive physical quality assessments, including organoleptic properties, moisture content, angle of repose, flow rate, dissolution time, and tapped density. Antioxidant activity was quantified using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, reporting IC50 values. All instant granule formulations successfully met the established physical quality requirements across all evaluated parameters. Furthermore, the antioxidant activity demonstrated a concentration-dependent effect, with IC50 values of 119.576 ppm for Formula 1, 82.000 ppm for Formula 2, and 59.962 ppm for Formula 3. This study confirms that instant granules formulated with a single black A. sativum extract exhibit significant antioxidant potential and possess desirable physical characteristics, indicating their promise as a natural antioxidant supplement.